Gaya Bahasa Dalam Lirik Lagu Kaze Wo Hamu Karya N-Buna - Hastuti, Nur (Vocational College of Diponegoro University, 2021)
Music is a work of art in the form of a song that expresses the feelings of its creator through the main elements of music, namely rhythm, melody, harmony and others. The purpose of this study was to determine the style of language in the lyrics of the song kaze wo hamu by n-buna. The method uses stylistics. Based on the results of research and discussion on the lyrics of the song kaze wo hamu by n-buna, it is found that there is a style of language. Hyperbole is 6, repetition is 3, personification is 2, synesthesia is 2, and tautology is 1. The existence of language style in a song lyric further enhances the meaning to be conveyed to music lovers.